A Surface Ocean CO2 Reference Network, SOCONET and Associated Marine Boundary Layer CO2 Measurements - Wanninkhof, Rik; Pickers, Penelope A.; Omar, Abdirahman M.; Sutton, Adrienne; Murata, Akihiko; Olsen, Are; Stephens, Britton B.; Tilbrook, Bronte; Munro, David; Pierrot, Denis; Rehder, Gregor; Santana-Casiano, J. Magdalena; et al. (Frontiers in Marine Science, 2019)
The Surface Ocean CO2 NETwork (SOCONET) and Marine Boundary Layer (MBL) CO2 measurements from ships and buoys focus on the operational aspects of measurements of CO2 in both the ocean surface and atmospheric marine boundary layers. The focus is on providing accurate pCO2 data to within 2 micro atmosphere (µatm) for surface ocean and 0.2 parts per million (ppm) for MBL measurements following rigorous best practices, calibration and intercomparison procedures. Platforms and data will be tracked in near real-time and final quality-controlled data will be provided to the community within a year. The network involving partners worldwide will enable production of important products such as maps of monthly resolved surface ocean CO2 and air-sea CO2 flux measurements. These products and other derivatives using surface ocean and MBL CO2 data, such as surface ocean pH maps and MBL CO2 maps, will be of high value for policy assessments and socio-economic decisions regarding the role of the ocean in sequestering anthropogenic CO2 and how this uptake is impacting ocean health by ocean acidification. SOCONET has an open ocean emphasis and aims to work closely with regional (coastal) networks and liaise with intergovernmental science organizations such as Global Atmosphere watch (GAW), and the joint WMO-IOC committee for and ocean and [marine] meteorology (JCO[M]M). Here we describe the details of this emerging network and its proposed operations and practices.